Intentions Undercover - Hiding Intentions is Considered Unfair - Tim Friehe; Verena Utikal (Center for Economic Studies and ifo Institute (CESifo), 2015)
Unfair intentions provoke negative reciprocity from others, making their concealment potentially beneficial. This paper explores whether people hide their unfair intentions from others and how hiding intentions is itself perceived in fairness terms. Our experimental data show a high frequency of cover-up attempts and that affected parties punish the concealment of intentions, establishing that people consider not only unkind intentions but also hiding intentions unfair. When choosing whether or not to hide intentions, subjects trade-off the lower expected punishment when the cover up of unfair intentions is successful against the higher expected punishment when cover up is unsuccessful. In an attempt to better understand fairness perceptions, we present a typology of punisher types and show that hiding unkind intentions is treated differently than unkind intentions, possibly establishing a behavioral category of its own.
Keywords: C90; D01; K42; 330; intentions; reciprocity; fairness; avoidance; cover up; experiment